Feasibility and preliminary outcomes of compassion-focused acceptance and commitment therapy delivered via telehealth in a community behavioral health clinic - Kleiman, Keryn; Marks, Donald R.; Block-Lerner, Jennifer; Tirch, Dennis; Brady, Victoria; Foote, Benjamin; Silberstein-Tirch, Laura (Frontiers in Psychology, 2025)
IntroductionGiven the significant roles self-criticism and shame can play in the development and maintenance of psychological disorders, several compassion-based treatments, such as compassion-focused therapy (CFT), have been developed in recent years to address shame-based difficulties across a range of psychopathological conditions. CFT aligns with major tenets of acceptance and commitment therapy (ACT), which has been shown to be effective in treating various clinical disorders. Compassion focused acceptance and commitment therapy (CFACT) merges elements of CFT and ACT.MethodThis study examined the feasibility, acceptability, and preliminary outcomes of a manualized CFACT protocol for transdiagnostic presentations in a community behavioral health clinic through a non-concurrent multiple baseline single-case experimental design. Participants received the therapy over 16–19 weekly sessions. Symptom severity, self-compassion, guilt, shame, attributional styles (detachment and externalization of blame), psychological flexibility, functioning in valued life contexts, and quality of life were assessed across baseline and treatment phases. Ratings of perceived utility and other aspects of interest/receptivity were also collected.ResultsResults indicate strong acceptability and receptivity for CFACT across both participants and clinicians. Training clinicians in CFACT and implementing the treatment over telehealth in a training clinic setting was feasible. Most participants exhibited reliable decreases in symptom distress and psychological inflexibility, and reliable increases in self-compassion. Detachment level increased for most participants. Trajectories of guilt-proneness, shame-proneness, externalization of blame, and quality of life either varied across participants or remained unchanged. Supplemental cross-lagged correlation analyses did not demonstrate predictive associations between variables.DiscussionWhile quantitative outcome results were mixed, preliminary evidence suggests CFACT contributes to reduced symptom distress and increased psychological flexibility, self-compassion, and detached attributional style. Limitations and future directions are discussed.